Load‐aware user association with quality of service support in heterogeneous cellular networks. Issue 4 (1st March 2015) - Zhou, Tianqing; Huang, Yongming; Fan, Lixing; Yang, Luxi
Abstract : In this study, the authors propose a user association scheme with quality of service support for load balancing in heterogeneous cellular networks (HCNs), which jointly considers user's achievable rate and load level of each BS instead of only utilising the former. To reveal how HCNs should self‐organise, the authors formulate it as a network‐wide weighted utility maximisation problem. Note that the formulated problem is a non‐linear mixed‐integer one, and its optimal solutions may be very difficult to be found when it is large‐scale. To solve the proposed problem, the authors design a low‐complexity distributed algorithm via dual decomposition. Numerical results show that, compared with the range expansion association (REA) and best power association (BPA), the strategy has a higher load balancing level (LBL) and a lower call blocking probability (CBP). Meanwhile, the proposed algorithm occupies a very fast convergence rate when its parameters are set properly.